Pre-hatching embryo-dependent and -independent programming of endometrial function in cattle - Sponchiado, Mariana (2017)
The bovine pre-implantation embryo secretes bioactive molecules from early development stages, but effects on endometrial function are reported to start only after elongation. Here, we interrogated spatially defined regions of the endometrium transcriptome for responses to a day 7 embryo in vivo. We hypothesize that exposure to an embryo changes the abundance of specific transcripts in the cranial region of the pregnant uterine horn. Endometrium was collected from the uterotubal junction (UTJ), anterior (IA), medial (IM) and posterior (IP) regions of the uterine horn ipsilateral to the CL 7 days after estrus from sham-inseminated (Con) or artificially inseminated, confirmed pregnant (Preg) cows. Abundance of 86 transcripts was evaluated by qPCR using a microfluidic platform. Abundance of 12 transcripts was modulated in the Preg endometrium, including classical interferon-stimulated genes (ISG15, MX1, MX2 and OAS1Y), prostaglandin biosynthesis genes (PTGES, HPGD and AKR1C4), water channel (AQP4) and a solute transporter (SLC1A4) and this was in the UTJ and IA mainly. Additionally, for 71 transcripts, abundance varied according to region of the reproductive tract. Regulation included downregulation of genes associated with proliferation (IGF1, IGF2, IGF1R and IGF2R) and extracellular matrix remodeling (MMP14, MMP19 and MMP2) and upregulation of anti-adhesive genes (MUC1) in the cranial regions of uterine horn. Physical proximity to the embryo provides paracrine regulation of endometrial function. Embryo-independent regulation of the endometrial transcriptome may support subsequent stages of embryo development, such as elongation and implantation. We speculate that successful early embryo-dependent and -independent programming fine-tune endometrial functions that are important for maintenance of pregnancy in cattle.